Artificial Diels–Alderase based on the transmembrane protein FhuA - Osseili, Hassan (Beilstein J Org Chem, 2016)
Copper(I) and copper(II) complexes were covalently linked to an engineered variant of the transmembrane protein Ferric hydroxamate uptake protein component A (FhuA ΔCVF(tev)). Copper(I) was incorporated using an N-heterocyclic carbene (NHC) ligand equipped with a maleimide group on the side arm at the imidazole nitrogen. Copper(II) was attached by coordination to a terpyridyl ligand. The spacer length was varied in the back of the ligand framework. These biohybrid catalysts were shown to be active in the Diels–Alder reaction of a chalcone derivative with cyclopentadiene to preferentially give the endo product.